Two Gold Hoards of the Late Kushans from Rustam, Khyber Pakhtunkhwa - Khan, Gul Rahim; Shakirullah (Ancient Pakistan, 2021)
A hoard or a group of coins with its categorically stated find spot is brought here for the attention of scholars. Such hoards prove quite helpful in establishing circulation of particular coins at a certain period and place. The present lots of coins are important evidence concerning coinage and history of the Late Kushans in ancient Gandhara region.